Synthesis and electrocatalytic performance of spherical core-shell tantalum (oxy)nitride@nitrided carbon composites in the oxygen reduction reaction. (10th February 2017) - Wassner, M.; Eckardt, M.; Gebauer, C.; Bourret, G.R.; Hüsing, N.; Behm, R.J.
Graphical abstract: Highlights: Novel core-shell tantalum (oxy)nitride@nitrided carbon composites as ORR catalysts. Controlled synthesis by combined hydrothermal + sol-gel processing and nitridation. Nitrided carbon cores result in strongly improved electric conductivity. High conductivity goes along with high ORR activity. Oxygen reduction activity depends strongly on the nitridation temperature. Abstract: As part of an ongoing effort to develop novel, highly active and stable Pt-free catalysts for the oxygen reduction reaction (ORR), we here report the synthesis, structural characteristics and electrochemical/electrocatalytic properties of novel core-shell composite materials, consisting of a spherical nitrided carbon core and a tantalum (oxy)nitride shell. The (nitrided) carbon core is supposed to improve the electrical conductivity of the material and the (oxy)nitride shell is intended to protect the core against electrochemical corrosion. Spherical core-shell TaOx Ny @Cm Nn composite particles were synthesized by sol-gel deposition of tantalum oxide on preformed carbon spheres, which were prepared by hydrothermal carbonization of glucose and subsequent nitriding in ammonia vapor at different temperatures (700 °C − 1150 °C). The influence of the nitriding temperature on the structure and phase composition of the resulting composite particles was evaluated, employing a variety of techniques, including electron microscopy (SEM, TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), elemental analysis, thermogravimetric analysis (TGA), IR spectroscopy and N2 sorption measurements, and correlated with changes in the electrochemical/electrocatalytic behavior. These core-shell composite materials show a significantly improved ORR activity compared to pure tantalum (oxy)nitrides, in particular upon nitriding at 1000 °C, while the selectivity for the 4-electron pathway to H2 O still requires improvement. The physical origin of the high activity of these materials and contributions from different phases are discussed.